The unintended consequences of trade protection on the environment - Taipeng Li; Lorenzo Trimachi; Rui Xie; Guohao Yang (University College Dublin, UCD School of Economics, 2023)
We analyze the impact of a rise in protectionism on environmental regulation. Using the 2018 US-China trade war as a quasi-natural experiment, we find that higher exposure to tariffs leads to less stringent regulation targets in China, increasing air pollution and carbon emissions. Politically motivated changes in environmental policies rationalize our results: the central government and local party secretaries relax environmental regulations to mitigate the negative consequences of tariffs for polluting industries. We find heterogeneous effects depending on politicians' characteristics: younger, recently appointed, and more connected local politicians are more likely to ease environmental regulation. This policy reaction benefits politicians: prefectures with the most considerable easing in environmental regulation manage to curb the negative economic consequences of the trade war, while their mayors have a relatively larger probability of promotion. This paper presents the first empirical evidence of political incentives to manipulate environmental regulation to curb negative economic shocks.
Keywords: Q50; Q56; F13; F18; E32; D72; 330; Political Cycles; Environmental Regulation; Trade Protection; US-China Trade War